Inquiry-based Science Teaching through Constructionism: a path towards scientific literacy - Maria Josiane da Silva Nery; Fabiano Reis da Silva; Paulo César Geglio (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
Inspired by the concept of bricolage brought by Seymour Papert to education, this work articulated a theoretical and methodological set composed by Constructionism, Inquiry-based Science Teaching and Augmented Reality, aiming to achieve Scientific Literacy indicators. This articulation was concretized in a biology didactic planning, experienced in the second year of high school in a public school. The search for scientific literacy indicators was carried out by means of Textual Discourse Analysis. The results show that the theoretical-methodological set led the students to construct several indicators proposed in the literature of the area. We conclude that constructionist approaches via inquiry teaching are a viable path to scientific literacy and suggest that bricolage should be a strategy encouraged in basic education teacher training or improvement courses.